Logic of the tautologies (2012)
The deductive system LT: logic of tautologies is presented as an extension of the classical propositional calculus. In the LT system, the meta-logical notions of tautology, contradiction, satisfactory, refutable and contingency are formalized. The LT system is characterized with a Kripke-style semantics, and can be seen as an extension of the S5 modal logic system.